Aerodynamic Characteristics and Flow Patterns of Square Cylinders with Rounded Facet - Biswas, Nripendranath (MIST International Journal of Science and Technology, 2025)
This study experimentally investigates the effect of facet width on the static pressure distribution around a single square cylinder with rounded facets. Experiments are conducted in an open-circuit wind tunnel at a Reynolds number of 5.4 × 10⁴, based on the side dimension of the cylinder subjected to a uniform flow velocity of 13.6 m/s. Five different dimensionless facet widths are systematically introduced to assess their influence on pressure distribution at varying angles of attack. Static pressure measurements are collected around the perimeter of the cylinder, and the resulting data are processed through numerical integration to determine the corresponding drag coefficients. The results demonstrate that incorporating facets significantly modifies the aerodynamic characteristics of the cylinder by reducing the drag coefficient compared to that of a sharp-edged configuration. The drag reduction is primarily attributed to delayed flow separation and a decrease in the size of the wake region. However, beyond a critical facet width, further increases produce only marginal improvements, indicating the presence of an optimal range for facet dimensions. This research demonstrates that facet modification is an effective and practical approach for controlling aerodynamic drag in bluff bodies. The findings offer valuable insights for optimizing structural designs subjected to wind loads, highlighting potential applications in civil engineering fields such as building design, bridge construction, and tower development. By deepening the understanding of how minor geometric alterations can impact flow behaviour, this work contributes to the development of safer, more efficient, and aerodynamically stable structures exposed to atmospheric winds. MIJST, Vol. 13, June 2025 : 01-08 DOI: https://doi.org/10.47981/j.mijst.13(01)2025.547(01-08)